Pills, power, and policy: the struggle for drug reform in Cold War America and its consequences - Tobbell, Dominique A (California/Milbank books on health and the public, 2011)
Since the 1950s, the American pharmaceutical industry has been heavily criticized for its profit levels, the high cost of prescription drugs, drug safety problems, and more, yet it has, together with the medical profession, staunchly and successfully opposed regulation.Pills, Power, and Policyoffers a lucid history of how the American drug industry and key sectors of the medical profession came to be allies against pharmaceutical reform. It details the political strategies they have used to influence public opinion, shape legislative reform, and define the regulatory environment of prescription drugs. Untangling the complex relationships between drug companies, physicians, and academic researchers, the book provides essential historical context for understanding how corporate interests came to dominate American health care policy after World War II.